Sunlight Exposure on Sars-Cov-2 Samples; Descriptive Analysis - Bhatti, Shameem; Kumar, Pardeep; Ali, Waheed; Hassan, Syed Mujahid; Bhatti, Naseem Khatoon; Ahuja, Kanta (Journal of Liaquat University of Medical & Health Sciences, 2022)
ABSTRACT OBJECTIVE To evaluate the effect of sunlight on PCR positivity of SARS-COV-2 positive samples in Pakistan. METHODOLOGY After institutional approval, naso-pharyngeal swab samples were taken from eight positive (ascertained by PCR) nCovid-19 patients were obtained and divided into numerous units so that sample of each individual patient could be tested 12 times by PCR (inclusive of six controls and six tests samples). Six control samples were kept in laboratory environment while six were kept in sunlight (each for a differing duration i.e. 0, 5, 15, 30, 60 and 120 minutes) and the temperature and humidity levels recorded. A sample will undergo PCR test (along with its time matched control at 0, 5, 15, 30, 60 and 120 minutes and its SARS-COV-2 positivity recorded. Following the experiment, the samples shall be discarded as per institutional protocol. RESULTS Among the 8 samples (each tested in six different batches after exposure to sunlight for varying amounts of time), most i.e. 45 (93.75%) tested positive for SARS-COV-2. However, there may be a relationship between length of exposure to sunlight and PCR positivity of the samples, since all 3 samples that tested negative were exposed to sunlight for more at least 30 minutes. All controls (placed in laboratory and not exposed to sunlight, tested positive). CONCLUSION The results reveal that effect of sunlight on PCR positivity of SARS-COV-2, is not clear and despite international use of UV light for disinfection, very limited success can be achieved by exposure to plain sunlight. Keywords SARS-COV-2, nCovid-19, Ultraviolet Light, Sunlight PCR & UV Light and Nasopharangeal Swab.